2018
DOI: 10.1002/ece3.4369
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic trajectories of body coloration reveal its function as a multicomponent nonsenescent signal

Abstract: The understanding of developmental patterns of body coloration is challenging because of the multicomponent nature of color signals and the multiple selective pressures acting upon them, which further depend on the sex of the bearer and area of display. Pigmentary colors are thought to be strongly involved in sexual selection, while structural colors are thought to generally associate with conspecifics interactions and improve the discrimination of pigmentary colors. Yet, it remains unclear whether age depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Third, ontogenetic processes could also explain this relationship, which could be tested in longitudinal studies following the same males as they age. For example, Bonnaffé et al (2018) showed that, in male common lizards Zootoca vivipara, UV chroma increased with age, likely due to ontogenetic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Third, ontogenetic processes could also explain this relationship, which could be tested in longitudinal studies following the same males as they age. For example, Bonnaffé et al (2018) showed that, in male common lizards Zootoca vivipara, UV chroma increased with age, likely due to ontogenetic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Male common lizards display UV-reflecting signals on 107 their throat (Martin et al, 2013) that play a role during male-male competition (Martin et al, 108 2016) and female mate choice (Badiane et al, 2020). In addition, UV chroma on male throat 109 increases with age and body size (Bonnaffé et al, 2018). Altogether, these results strongly 110 suggest that male UV-reflecting throats might signal male quality in Z. vivipara.…”
mentioning
confidence: 84%
“…However, while UV features have been shown to correlated with bite force in wall lizards (Pérez i de Lanuza et al, 2014), it does not seem to be the case in Z. vivipara. Instead, UV features appear to correlate with male body size and sprint speed (Bonnaffé et al, 2018;unpublished results). Although we used a randomized experimental design, this result, along with the absence of effects of UV reflectance on female flips, could also be explained by the use of other signals modalities or cues by females, such as chemical signals.…”
Section: Pre-copulatory and Copulatory Behaviormentioning
confidence: 98%
“…In addition, the ventral coloration shows a secondary reflectance peak in the UV range, which is especially pronounced on males' throat (Martin et al, 2013). UV chroma of the throat and belly coloration increases with age and size in males (Bonnaffé et al, 2018).…”
Section: Study Speciesmentioning
confidence: 98%
See 1 more Smart Citation